PEMBUATAN TAHU SUSU MENGGUNAKAN KOAGULAN DARI BONGGOL NANAS (Ananas comosus L.) [MANUFACTURING MILK TOFU USING COAGULANTS FROM PINEAPPLE HUMPS (Ananas comosus L.)] - Pratama, Ryan; Handayani, Ratna (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2023)
Bromelain enzyme is a protease enzyme that can coagulate casein in milk. The use of pineapple waste, namely pineapple humps, can be used as a coagulant in making milk tofu. This research aimed to determine the best bromelain enzymes from two types of pineapple humps based on protein content and enzyme activity, as well as to analyzed the effect of bromelain enzyme crude extract concentration as a coagulant in making tofu with different heating temperatures. In phase I of the research, crude extract of bromelain enzymes was isolated and analyzed by yield, protein content, and enzyme activity. In phase II, milk tofu was made using a crude enzyme extract concentration of 0.50%; 1,00%; and 1.50% with a clotting temperature of 60 oC and 80 oC which were then analyzed by yield, water content, fat content, ash content, protein content, color and texture. The results of phase I analysis showed that the best type of humps was Queen pineapple humps with protein content of 0.12 ± 0.007 µg/ml and activity of 76.27 ± 4.43 U/ml, subsequently the humps were used for phase II analysis. The best treatment from phase II research was a crude enzyme extract concentration of 1.0% and a clotting temperature of 80oC with a yield value of 24.27 ± 0.01%, a moisture content of 68.89 ± 3.30% and a protein content of 4.64 ± 0.008%. Bahasa Indonesia Abstract:Enzim bromelin merupakan enzim protease yang dapat menggumpalkan kasein pada susu. Penggunaan limbah nanas yaitu bonggol nanas dapat digunakan sebagai koagulan dalam pembuatan tahu susu. Penelitian ini bertujuan untuk menentukan ekstrak kasar enzim bromelin terbaik dari dua jenis bonggol nanas berdasarkan kadar protein dan aktivitas enzimnya, serta untuk menganalisis pengaruh konsentrasi ekstrak kasar enzim bromelin sebagai koagulan dalam pembuatan tahu dengan suhu pemanasan yang berbeda. Pada penelitian tahap I dilakukan ekstrak kasar enzim bromelin diisolasi dan dianalisis secara rendemen, kadar protein, dan aktivitas enzim. Pada tahap II dilakukan pembuatan tahu susu menggunakan konsentrasi ekstrak kasar enzim 0,50%; 1,00%; dan 1,50% dengan suhu penggumpalan 60 oC dan 80 oC yang selanjutnya dianalisis secara rendemen, kadar air, kadar lemak, kadar abu, kadar protein, warna dan tekstur. Hasil analisis tahap I menunjukkan bahwa jenis bonggol terbaik adalah bonggol nanas Queen dengan kadar protein 0,12 ± 0,007 µg/ml dan aktivitas 76,27 ± 4,43 U/ml, selanjutnya bonggol tersebut digunakan untuk analisis tahap II. Perlakuan terbaik dari penelitian tahap II adalah konsentrasi enzim 1,0% dengan suhu penggumpalan 80 oC dengan nilai rendemen 24,27 ± 0,01%, nilai kadar air 68,89 ± 3,30% dan nilai kadar protein 4,65 ± 0,008%.